Nitrogen, lignin, cellulose and ADSS [Acid-Detergent Soluble Substances] dynamics during decomposition of Pinus nigra Arn. needles assessed by direct field measurements - Vittozzi P.; De Marco A.; Virzo de Santo A. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
In a P. nigra Arn. forest, implanted on volcanic lapillus of the last eruption of the Vesuvius (1944), litter mass loss and the dynamics of nitrogen and organic-chemical constituents was studied without enclosing the needles in litter-bags. The vertical distribution of fungi within the different litter layers was also examined. The dynamics of needle litter decomposition showed a rapid mass-loss phase followed by a slow mass-loss phase; the accumulated mass loss reached an asymptotic level at about 50 percent of the initial mass. During decomposition nitrogen was released since the early stage. As much as 72 percent of the original mass of lignin, 60 percent and 20 percent of the original mass of ADSS and cellulose, respectively, were found in the far decomposed litter. The amount of total and live fungal mycelium was similar in La (light-brown needles) and Lb (dark-brown needles) and increased in Lc (brown-black needles) and Ld (black needles) layers.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)